1994
DOI: 10.1016/0014-5793(94)00919-8
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Fe–O2 and FeIV=O stretching Raman bands for dioxygen reduction intermediates of cytochrome bo isolated from Escherichia coli

Abstract: Reaction intermediates in dioxygen reduction by the E. coli cytochrome bo-type ubiquinol oxidase were studied by time-resolved resonance Raman spectroscopy using the artificial cardiovascular system. At O-20 ps following photolysis of the enzyme-CO adduct in the presence of 0,, we observed the Fe&& stretching Raman band at 568 cm-' which shifted to 535 cm-' with the "0, derivative. These frequencies are remarkably close to those of other oxyhemoproteins including dioxygen-bound hemoglobin and aa,-type cytochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
6
23
1
Order By: Relevance
“…The resulting "oxy" (O) intermediate is rapidly transformed to the so-called "peroxy" (P) species, which has an oxidation state of the hemecopper moiety higher than the Fe 3ϩ /Cu 2ϩ state by two oxidative equivalent. Although the peroxy intermediate had been expected to have an intact O-O bond (11,12), our previous studies have clearly shown the definite FeϭO stretching Raman band at ϳ800 cm Ϫ1 for the P intermediate, suggesting that the O-O bond is already cleaved at this step (13)(14)(15)(16). Other chemical experiments also support this assignment (17,18).…”
supporting
confidence: 56%
“…The resulting "oxy" (O) intermediate is rapidly transformed to the so-called "peroxy" (P) species, which has an oxidation state of the hemecopper moiety higher than the Fe 3ϩ /Cu 2ϩ state by two oxidative equivalent. Although the peroxy intermediate had been expected to have an intact O-O bond (11,12), our previous studies have clearly shown the definite FeϭO stretching Raman band at ϳ800 cm Ϫ1 for the P intermediate, suggesting that the O-O bond is already cleaved at this step (13)(14)(15)(16). Other chemical experiments also support this assignment (17,18).…”
supporting
confidence: 56%
“…Time‐resolved resonance Raman studies showed the formation of the oxoferryl intermediate with a rate constant of about 2×10 4 s −1 [20,21] which is comparable to about 5×10 4 s −1 for the fast phase observed by visible spectroscopy [13,16,19,22]. The final product of the fast reaction with peaks at 557 and about 420 nm could be the oxoferryl intermediate [19] which then decays to the oxidized state within 1 s [13,16,21,22].…”
Section: Resultsmentioning
confidence: 74%
“…Although the dioxygen reduction mechanism at the hemecopper binuclear center is thought to be identical in both enzymes (12)(13)(14), these differences raise the questions whether the electron transfer reactions from the substrates to dioxygen and the proton pumping mechanism coupled to these redox reactions are alike or distinct. It is proposed that the last two steps of the four-electron transfer reactions to dioxygen are linked to proton pumping by cytochrome c oxidase (15)(16)(17).…”
mentioning
confidence: 99%